2018
DOI: 10.3390/ijms19113449
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hydroxyproline-Containing Hairpin-Like Antimicrobial Peptide EcAMP1-Hyp from Barnyard Grass (Echinochloa crusgalli L.) Seeds: Structural Identification and Comparative Analysis of Antifungal Activity

Abstract: Herein, we describe a modified form of the antimicrobial hairpin-like peptide EcAMP1, isolated from barnyard grass (E. crusgalli) seeds, which is structurally characterized by a combination of high-pressure liquid chromatography, mass spectrometry, and automated Edman sequencing. This derivate has a single amino acid substitution (Pro19Hyp) in the second α-helical region of the molecule, which is critical for the formation of the hydrophobic core and the secondary structure elements. Comparing the antifungal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…This confirms a critical role of tryptophan residue located in the β-hairpin in antifungal and antibacterial activity. Moreover, the unusual natural form of the EcAMP1 peptide consisting of a substitution from proline to hydroxyproline at the 19th position demonstrated a weaker activity against a model plant pathogenic fungus F. solani [ 19 ]. In the case of EcAMP1-X4, the removal of six C-terminal amino acid residues concerns the second α-helix and might lead to a destabilization of the molecule structure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This confirms a critical role of tryptophan residue located in the β-hairpin in antifungal and antibacterial activity. Moreover, the unusual natural form of the EcAMP1 peptide consisting of a substitution from proline to hydroxyproline at the 19th position demonstrated a weaker activity against a model plant pathogenic fungus F. solani [ 19 ]. In the case of EcAMP1-X4, the removal of six C-terminal amino acid residues concerns the second α-helix and might lead to a destabilization of the molecule structure.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical synthesis of the truncated EcAMP1-X1 and EcAMP1-X2 was carried out as described earlier [ 19 ] with modifications [ 33 ]. Briefly, solid-phase peptide synthesis was performed on an automatic peptide synthesizer (Agilent Technologies, Santa Clara, CA, USA) based on the Gilson automated liquid handler system (Gilson Scientific Ltd., Dunstable, UK), according to Gilson application note 228 (Gilson Scientific Ltd., Dunstable, UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering this data and low antifungal activity, it was concluded that the tails of the molecule contributed either through direct interaction with the fungi or through stabilization of the helical structure (Slavokhotova et al, 2014b). Rogozhin et al (2018b) identified several structural elements of α-hairpinins that play a key role in their biological activity. According to their experiments and the literature data, the first crucial element is a β-hairpin structure (10-13 amino acid residues) that connects two α-helices.…”
Section: α-Hairpinins With Antifungal Activitymentioning
confidence: 99%
“…The second element is a mini-cluster of positively charged amino acid residues necessary for interaction with negatively charged carbohydrate components and polymers of fungal cell walls. And the third element is the presence of at least one hydrophobic residue (e.g., tryptophan) pivotal for binding with components of fungal cell membranes, including sphingolipids or ergosterols (Rogozhin et al, 2018b).…”
Section: α-Hairpinins With Antifungal Activitymentioning
confidence: 99%